ANALISIS EKSTASI KOMUNIKASI MEDIA SOSIAL YOUTUBE PADA YOUTUBER WINDA BASUDARA DENGAN KONTEN BERMAIN GAME - Almuhajirin, Muh Sahran; Basyir, Jalaluddin (KAGANGA KOMUNIKA: Journal of Communication Science, 2025)
This study aims to describe the representation of excessive pleasure (communication ecstasy) in gaming content on Winda Basudara's YouTube channel through an analysis of a 13.57-minute video titled “Bocil di Warung Kita Top Up In 1 Juta Rupiah di Free Fire!” The research problem stems from the phenomenon of increasing consumption of entertainment content that offers instant pleasure and shifts interest away from more educational content. The approach used is descriptive qualitative with Jean Baudrillard's simulacra theory framework. The analysis results show that the content exploits entertainment sensations through signs and symbols such as thumbnails, game characters, and diamond top-up practices that represent artificial forms of pleasure. The research results show that the representation of pleasure in the video is presented through symbolic manipulation of Money becoming Diamonds, Diamonds becoming Entertainment, and Entertainment bringing Popularity. In addition, Fathan's expressions of joy are exploited as viewing commodities, material values are transformed into symbolic values through game simulations, and excessive entertainment is presented, disconnecting concrete reality and creating hyperreality. Thus, pleasure is not just part of the video, but the main selling point that is deliberately produced to attract viewers and maximize profits through ecstatic viewing.   Keywords: Communication ecstasy, YouTube, Winda Basudara, Simulacra, Hyperreality